APPLICATION OF FINANCIAL STATEMENT PREPARATION BASED ON FINANCIAL ACCOUNTING STANDARDS FOR MICRO, SMALL AND MEDIUM ENTITIES IN MSMES (CASE STUDY OF TOKO ANJANI COLLECTION) - Pebri Anjani; Nurhayati Nurhayati (SEAN Institute, 2023)
This research is entitled